(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article scientifically and theoretically covers the strategies of an educational cluster in the organization of a production and educational cluster, the conditions and scientific factors for the effective development of an educational cluster, as well as the main goals of an educational cluster.